Relationship Of Characteristics With Work Fatigue In Oil Palm Harvesters In Afdeling V Ptpn Ii Palm Sebrang - manalu, gadis; Harahap, Reni Agustina (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2023)
Fatigue is a condition that can be experienced by workers, usually the fatigue is characterized by the weakening of the muscles in the workforce so that workers are unable to do their work again. The research aims to determine relationship of characteristics with work fatigue in oil palm harvesters in Afdeling V PTPN II Sawit Seberang in 2023. This is a quantitative research with a